Elevation of dopamine level reduces hostseeking activity in the adult female mosquito Aedes albopictus - Yuki, Fukumitsu; Keiichi, Irie; Tomomitsu, Satho; Hitoshi, Aonuma; Hamady, Dieng; Abu Hassan, Ahmad; Yukihiko, Nakashima; Kenichi, Mishima; Nobuhiro, Kashige; Fumio, Miake (Parasites & Vectors, 2012)
Background: Mosquito-borne viruses are transmitted to human hosts via blood-feeding behavior of female mosquitoes. Female mosquitoes seek a host to take blood meals (host-seeking behavior). In order to prevent virus infections, it is important to understand how they modulate host-seeking behavior. Dopamine (DA) in the central nervous system acts as a neuromediator that regulates a variety of behaviors in insects. In female mosquitoes, host-seeking behavior increases when DA levels in the head decline after emergence. However, it remains unclear whether DA directly modulates host-seeking behavior in female mosquitoes. The aim of this study was to examine whether changes in DA levels in the head affects host-seeking activity in the adult female mosquito Aedes albopictus (Ae. albopictus). Findings: We compared host-seeking behavior in one group of emerging female adults treated with L-β-3,4-dihydroxyphenylalanine (L-DOPA), the precursor of DA, (L-DOPA group), with that in an untreated control (control group) after confirming elevation of head DA in L-DOPA group by using high-performance liquid chromatography. The content of head DA in L-DOPA group significantly remained higher than that in controls on all days examined. The host-seeking activity in the control group showed a gradual increase over the 6-day experimental period. In contrast, there was no such increase in the host-seeking activity in the L-DOPA group. Therefore, the host-seeking activity of L-DOPA group was significantly lower than that of the controls between day 3 and 6 post-emergence. Conclusion: Our results indicate that elevation of DA level reduces host-seeking activity in adult female mosquito Ae. albopictus.